MACROPHAGES ARE UNSUCCESSFUL IN CLEARING AGGREGATED ALPHA-SYNUCLEIN FROM THE GASTROINTESTINAL TRACT OF HEALTHY AGED FISCHER 344 RATS - Phillips, Robert J. (2013)
With age, alpha-synuclein (α-SYNC) misfolds and forms insoluble deposits of protein in the myenteric plexus, leading presumably to dystrophy and degeneration in the circuitry controlling gastrointestinal (GI) function. The present experiment examined aggregates of α-SYNC in the aging small intestine and investigated how macrophages in the wall of the GI tract respond to these aberrant deposits. Groups of adult and aged Fisher 344 rats were studied. Whole mounts of duodenal, jejunal and ileal smooth muscle wall, including the myenteric plexus, were prepared. Double labeling immunohistochemistry was used to stain α-SYNC protein and the phenotypic macrophage antigens CD163 and MHCII. Alpha-synuclein accumulated in dense aggregates in axons of both postganglionic and preganglionic neurons throughout the small intestine. Staining patterns suggested that deposits of protein occur initially in axonal terminals and then spread retrogradely towards the somata. Macrophages that were adjacent to dystrophic terminal processes were swollen and contained vacuoles filled with insoluble α-SYNC, and these macrophages commonly had the phenotype of alternatively activated phagocytes. The present results suggest that macrophages play an active phagocytotic role in removing α-SYNC aggregates that accumulate with age in the neural circuitry of the gut. Our observations further indicate that this housekeeping response does not clear the protein sufficiently to eliminate all synucleinopathies or their precursor aggregates from the healthy aging GI tract. Thus, accumulating deposits of insoluble α-SYNC in the wall of the GI tract may contribute, especially when compounded by disease or inflammation, to the age-associated neuropathies in the gut that compromise GI function.